1995
DOI: 10.3354/dao020183
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Atlantic halibut Hippoglossus hippoglossus to infectious pancreatic necrosis virus

Abstract: lnfectious pancreatic necrosis virus (IPNV), serotype NI, isolated from Atlantic halibut Hippoglossus hippoglossus, was used to bath-challenge (2 X l o 5 0 TCIDso ml-' for 1 h) Atlantic halibut fry of different sizes at 12 and 15°C in 3 trials. In all trials, the fry challenged at 15°C experienced significantly higher cumulative mortality compared to the unchallenged fry. The smallest fry (mean weight 0.1 g) also experienced significantly higher mortality compared to the controls when infected at 12"C, whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
3
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
(24 reference statements)
2
34
3
2
Order By: Relevance
“…A similar virus was detected in Atlantic salmon, but the histo-pathologic lesions were different and mainly associated with a cardiomyopathy (Grotmol et al 1997a). Infectious pancreatic necrosis virus (IPNV) is a common pathogen of Atlantic salmon (Wolf 1988), and this virus has also been associated with mortalities of Atlantic halibut in Norway (Mortensen et al 1990, Biering et al 1994, Biering & Bergh 1996 and juvenile Atlantic halibut in Scotland (Rodger & Frerichs 1997). The histopathological lesions associated with IPNV infections of Atlantic halibut larvae varied distinctly from those of Atlantic salmon fry.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar virus was detected in Atlantic salmon, but the histo-pathologic lesions were different and mainly associated with a cardiomyopathy (Grotmol et al 1997a). Infectious pancreatic necrosis virus (IPNV) is a common pathogen of Atlantic salmon (Wolf 1988), and this virus has also been associated with mortalities of Atlantic halibut in Norway (Mortensen et al 1990, Biering et al 1994, Biering & Bergh 1996 and juvenile Atlantic halibut in Scotland (Rodger & Frerichs 1997). The histopathological lesions associated with IPNV infections of Atlantic halibut larvae varied distinctly from those of Atlantic salmon fry.…”
Section: Introductionmentioning
confidence: 96%
“…The histopathological lesions associated with IPNV infections of Atlantic halibut larvae varied distinctly from those of Atlantic salmon fry. The most characteristic lesion was focal liver necrosis in halibut (Biering et al 1994) and no pancreatic lesions that typify IPNV infection of salmonids were seen (Ferguson 1989). Pancreatic acinar cell necrosis was described in halibut 'fry' infected with IPNV (Rodger & Frerichs 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, since the early 1990s, the amount of experience and knowledge of diseases of viral, bacterial or parasitical etiology of the Atlantic halibut has grown significantly. The evidence for the importance of diseases that affect the early life stages, such as infections by birnaviruses (Biering et al 1994), nodaviruses (Grotmol et al 1995(Grotmol et al , 1997, or various opportunistic bacteria (Bergh et al 1992b) has now been demonstrated by different challenge experiments (Table 1).The parasite fauna of wild Atlantic halibut have not been widely studied, for which reason our knowledge of potential harmful parasites in farmed fish is limited. Studies of parasites on wild halibut have mainly concentrated on describing metazoan parasites, particularly helminths (e.g.…”
mentioning
confidence: 99%
“…Furthermore, isolates from salmonids have been found to establish an infection in halibut (Biering 1997b), so that transfer of virus between salmon and halibut cannot be excluded. There is reason to believe that IPNV is widespread in Norwegian halibut stocks (Biering 1997b), captive as well as wild.On the basis of challenge experiments with halibut fry (Biering et al 1994) and yolk-sac larvae (Biering & Bergh 1996) it has been concluded that the virus is the cause of the disease. Temperature influenced mortality, as fry challenged at 15°C had significantly higher mortality than fry challenged at 12°C (Biering et al 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation